The Chicago School of Sociology and Youth Research: The Legacy of W. I. Thomas. From the Polish Peasant in Europe and America to the Child in America - Merico, Maurizio (Italian Sociological Review, 2020)
During his career, William I. Thomas richly contributed to the development of youth research, both within the University of Chicago and outside the academy, in contact with social agencies. Moving from a broad focus on the studies carried out by the Chicago School of Sociology, the paper aims at tracing Thomas’ contribution and legacy to the advancement of youth research, in order to recognise his influence on the definition of the fields of investigation, the theories, and the research methods employed. The paper first considers the analysis of the women reformers affiliated with the Hull House. The core of the analysis aims at re-evaluating Thomas’ contribution, taking into specific consideration three of his works. On this basis, in the last section, the paper attempts to recover his legacy through the studies carried out by the young scholars who worked at the Department of Sociology and in its affiliated institutes and projects. Paying specific attention to the suggestions he offered, with specific reference to the analysis of the lives of young people with migrants background, young women and the programs for the treatment of delinquency, helps to identify the main strengths and challenges of the first comprehensive study of ‘urban youth’, that – over time – have inspired fruitful perspectives of analysis and important research experiences.